Bandwidth management and monitoring for IP network traffic : an investigation - Irwin, Barry Vivian William (Rhodes University, Faculty of Science, Department of Computer Science, 2001)
Bandwidth management is a topic which is often discussed, but on which relatively little work has been done with regard to compiling a comprehensive set of techniques and methods for managing traffic on a network. What work has been done has concentrated on higher end networks, rather than the low bandwidth links which are commonly available in South Africa and other areas outside the United States. With more organisations increasingly making use of the Internet on a daily basis, the demand for bandwidth is outstripping the ability of providers to upgrade their infrastructure. This resource is therefore in need of management. In addition, for Internet access to become economically viable for widespread use by schools, NGOs and other academic institutions, the associated costs need to be controlled. Bandwidth management not only impacts on direct cost control, but encompasses the process of engineering a network and network resources in order to ensure the provision of as optimal a service as possible. Included in this is the provision of user education. Software has been developed for the implementation of traffic quotas, dynamic firewalling and visualisation. The research investigates various methods for monitoring and management of IP traffic with particular applicability to low bandwidth links. Several forms of visualisation for the analysis of historical and near-realtime traffic data are also discussed, including the use of three-dimensional landscapes. A number of bandwidth management practices are proposed, and the advantages of their combination, and complementary use are highlighted. By implementing these suggested policies, a holistic approach can be taken to the issue of bandwidth management on Internet links.
Keywords: TCP/IP (Computer network protocol); Computer networks; Electronic data processing -- Management; Computer networks -- Management